2019
DOI: 10.1108/ijqss-08-2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of resources, actors and contexts for value creation

Abstract: Purpose This paper aims to deepen the understanding of resource integration for value co-creation within service-dominant logic (SDL), by drawing on key knowledge management (KM) concepts. Design/methodology/approach This conceptual study introduces three key KM concepts, namely, object, agent and context to SDL; thus, deepening the understanding of how resources are becoming when actors are engaged in co-creating value-in-context. Findings This paper extends understanding of actors’ uses of knowledge in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Figure 4 shows the relationship between facilitators and the outcome of their success. Through the survey, we identified four factors as facilitators, including top management participation and support (Ali et al, 2018;Gopalakrishna-Remani et al, 2019;Kearns, 2006;Shao, 2019;Teubner, 2013); active communication and knowledge sharing between business and IT sectors (Arvidsson et al, 2014;Carrillo et al, 2019;Philip, 2009;Yeh et al, 2011); consideration of internal and external environments (Chi et al, 2005;Hung et al, 2016;Mirchandani and Lederer, 2012;Newkirk et al, 2008), and adequate resource allocation for SISP (Lientz, 2010;Samaha and Baki, 2009;Wallace, 2013). In addition, we confirmed that the four facilitators have a positive effect on business and IT alignment.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 shows the relationship between facilitators and the outcome of their success. Through the survey, we identified four factors as facilitators, including top management participation and support (Ali et al, 2018;Gopalakrishna-Remani et al, 2019;Kearns, 2006;Shao, 2019;Teubner, 2013); active communication and knowledge sharing between business and IT sectors (Arvidsson et al, 2014;Carrillo et al, 2019;Philip, 2009;Yeh et al, 2011); consideration of internal and external environments (Chi et al, 2005;Hung et al, 2016;Mirchandani and Lederer, 2012;Newkirk et al, 2008), and adequate resource allocation for SISP (Lientz, 2010;Samaha and Baki, 2009;Wallace, 2013). In addition, we confirmed that the four facilitators have a positive effect on business and IT alignment.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Further, it helps organizational members achieve mutual trust and credibility of IT (Oyemomi et al, 2019;Philip, 2007, Wallace, 2013 and diminishes costs and risks (Al Nahyan et al, 2019;Pai, 2006;Segars and Grover, 1999;Yeh et al, 2011). Effective communication and knowledge sharing between business and IT sectors plays an important role in facilitating the quality of SISP and the level of SISP success (Byrd et al, 2006;Lee and Bai, 2003;Pai, 2006;Teubner, 2013;Yeh et al, 2011) based on the achievement of effective business and IT alignment (Carrillo et al, 2019;Shao, 2019;Gutierrez et al, 2009;Ilmudeen et al, 2019;Maharaj and Brown, 2015;Pai, 2006;Reich and Benbasat, 2000). Therefore, the following hypothesis is proposed:…”
Section: Active Communication and Knowledge Sharing Between Business And It Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Such alignment efforts can occur in different organizational environments, although in this paper the authors focus on complex networked cyber-physical systems in an Industry 4.0 context. Approaches to qualitatively model organizational alignment have been proposed by several scholars [8][9][10][11][12][13][14]. Less common are approaches that allow quantifying the organizational alignment [2], where the alignment status of each node is known at each discrete time interval.…”
Section: Introductionmentioning
confidence: 99%
“…These alignment efforts can occur in different organizational settings, although, in this paper the authors focus on complex networked cyber-physical systems in an Industry 4.0 context. Scholars have proposed approaches to qualitatively model organizational alignment [12][13][14][15][16][17][18][19][20]. Approaches that allow for a quantification of organizational alignment are less common [2], which shows the alignment state of each node is known at each discrete time interval.…”
Section: Introductionmentioning
confidence: 99%